Inactivation of human plasma alters the structure and biomechanical properties of engineered tissues - Rosell-Valle, Cristina; Martín-López, María; Campos, Fernando; Chato-Astrain, Jesús; Campos-Cuerva, Rafael; Alaminos, Miguel; Santos González, Mónica (Frontiers in Bioengineering and Biotechnology, 2022)
Fibrin is widely used for tissue engineering applications. The use of blood derivatives, however, carries a high risk of transmission of infectious agents, necessitating the application of pathogen reduction technology (PRT). The impact of this process on the structural and biomechanical properties of the final products is unknown. We used normal plasma (PLc) and plasma inactivated by riboflavin and ultraviolet light exposure (PLi) to manufacture nanostructured cellularized fibrin-agarose hydrogels (NFAHs), and then compared their structural and biomechanical properties. We also measured functional protein C, prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT) and coagulation factors (fibrinogen, Factor [F] V, FVIII, FX, FXI, FXIII) in plasma samples before and after inactivation. The use of PLi to manufacture cellularized NFAHs increased the interfibrillar spacing and modified their biomechanical properties as compared with cellularized NFAH manufactured with PLc. PLi was also associated with a significant reduction in functional protein C, FV, FX, and FXI, and an increase in the international normalized ratio (derived from the PT), APTT, and TT. Our findings demonstrate that the use PRT for fibrin-agarose bioartificial tissue manufacturing does not adequately preserve the structural and biomechanical properties of the product. Further investigations into PRT-induced changes are warranted to determine the applications of NFAH manufactured with inactivated plasma as a medicinal product.